061 T cell-mediated cerebellitis after ipilimumab for small cell lung cancer. Issue 6 (27th May 2022) - Guillochon, Remi; Nolan, Luke; Nicoll, James; Jogai, Sanjay; Joseph-Pietras, Deborah; Arriola, Edurne; Ottensmeier, Christian; Galea, Ian
Abstract : Ipilimumab is an anti-CTLA4 antibody in evaluation for the treatment of small cell lung cancer. We report a case of rapidly progressive fatal cerebellitis occurring eight months after first dosing. Pre-treatment weakly positive anti-Yo antibodies did not change. Clinically asymptomatic anti-voltage-gated calcium channel antibodies developed after ipilimumab treatment, despite lack of expression by the tumour. The patient died three weeks into the neurological illness. Post-mortem examination revealed a T cell-mediated cerebellitis, with CD8 cytotoxicity towards Purkinje cells. This demonstrates the potential for CD8 T cells to trigger neuronal autoimmunity, offering insight into the early events in paraneoplastic neurological disease. remi.guillochon@nhs.net